Maintaining Boundaries: Masculinizing Fatherhood in the Feminine Province of Parenting - Hauser, Orlee (Qualitative Sociology Review, 2015)
Today’s fathers are more involved with childcare than the generations that preceded them. There is evidence to suggest that men consider fatherhood and their relationships with their children as more important than ever before. Still, society generally deems the activity of “parenting” as feminine. Thus, men who choose to identify with hegemonic notions of masculinity have few pre-existing father identities to choose from. I argue that fathers actively masculinize their parenting in order to protect their masculine identities. I use qualitative methods to examine the different approaches that they take to conciliate their actions as fathers with their identities as men. They do so by stressing different areas of importance when it comes to parenting, by adding masculine elements to their fathering activities, and by staying away from parenting activities that are generally marked by society as feminine.